Beyond Monumentality: Al-Masjid Al-Haram as Sacred Infrastructure, Pilgrimage Governance, and the Ethics of Public Care in Contemporary Islam - Abdulmalik Abdulkarim Omuya Adubi (Asian Journal of Islamic Studies and Da'wah, 2026)
Al-Masjid al-Haram, home to the Kaʿbah in Makkah, constitutes the direction of the qiblah and the ritual center of Hajj and Umrah. Although commonly approached primarily as a monumental sacred space, its expanding scale, complex infrastructure, and capacity to accommodate millions of worshippers require a broader understanding of its religious, institutional, and ethical functions. This article conceptualizes al-Masjid al-Haram as an integrated sacred ecosystem connecting revelation, ritual, architecture, environmental management, accessibility, crowd mobility, urban transformation, and public service. It develops six interconnected arguments: the mosque derives its primary significance from its Qurʾanic sanctity, Abrahamic origins, and centrality to Islamic worship; its operation depends on extensive systems of sanitation, cooling, water provision, wayfinding, crowd management, communication, maintenance, and accessibility; these systems demonstrate substantial state administrative and technical capacity; the facilitation of worship embodies Qurʾanic and Prophetic injunctions concerning ease and public care; the mosque represents an ideal of the public good that exposes tensions between effective pilgrimage administration and persistent public-service challenges across many Muslim societies; and its governance reflects a political theology of custodianship in which ritual pressures have generated new approaches to infrastructure and crowd control. The article concludes that the Grand Mosque creatively reconciles sanctity with renewal, equality with infrastructure, and worship with governance. This perspective extends discussions of sacred architecture beyond monumentality by framing pilgrimage infrastructure and institutional administration as ethical expressions of religious custodianship and public care.